Bioremediation of chlorophenol-contaminated sawmill soil using pilot-scale bioreactors under consecutive anaerobic-aerobic conditions. (July 2019) - Lopez-Echartea, Eglantina; Strejcek, Michal; Mateju, Vit; Vosahlova, Simona; Kyclt, Robin; Demnerova, Katerina; Uhlik, Ondrej
Abstract: Chlorophenols (CPs), including pentachlorophenol (PCP), are chemicals of concern due to their toxicity and persistence. Here we describe a successful reactor-based remediation of CP-contaminated soil and assess changes in the toxicity patterns and bacterial communities during the remediation. The remediation consisted of separating half of the contaminated soil to be ground (samples M) in order to test whether the grinding expedited the remediation, the other half was left unground (samples P). Both soils were mixed with wastewater treatment sludge to increase their bacterial diversity and facilitate the degradation of CPs, and the resultant mixtures were placed in 2 bioreactors, M and P, operated for 16 months under anaerobic conditions to favor dehalogenation and for an additional 16 months under aerobic conditions to achieve complete mineralization. Samples were taken every 4 months for toxicity and microbial analyses. The results showed a 64% removal of total CPs (ΣCPs) in reactor P after just 18 months of remediation, whereas similar depletion in reactor M occurred after ∼25 months, indicating that the grinding decelerated the remediation. By the end of the experiment, both reactors achieved 93.5–95% removal. The toxicity tests showed a decrease in toxicity as the remediation progressed. The succession of bacterial communities over time was significantly associated with pH, anaerobic/aerobic phase and the concentration of the majority of CP congeners. Our data indicate that the supplementation of contaminated soil with sludge and further incubation in pilot-scale bioreactors under consecutive anaerobic-aerobic conditions proved to be effective at the remediation of CP-contaminated soil. Highlights: Successful reactor-based remediation of CP-contaminated soil is described. 93.5–95% CPs were removed by the reactors described. The toxicity tests showed a decrease in toxicity as the treatment progressed. Bacterial communities were significantly associated with pH and CP concentrations.